2016
DOI: 10.1108/caer-05-2014-0045
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of the effect of crop insurance on farmers’ income: results from Inner Mongolia in China

Abstract: Purpose The purpose of this paper is to assess the effect of crop insurance on farmer income in Inner Mongolia, China Design/methodology/approach We use a survey of farmers in Inner Mongolia, China, with difference-in-difference, propensity score matching, and hybrid propensity score matching difference-in-difference treatment effect estimators to assess the effectiveness of crop insurance on farmer income. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 12 publications
5
25
0
2
Order By: Relevance
“…Ifft et al (2014) showed that farm value increased when fields are insured. Kuethe and Morehart (2012) proved that crop insurance improved farmlevel profit in the USA while Zhao et al (2016) did not demonstrate such effect in China. By contrast, only one study by Roberts et al (2003) considered the influence of crop insurance on pesticide use with contrasted results according to the crops considered: they reported a modest reduction of chemical input applications on tobacco and cotton crops and a modest increase on corn.…”
Section: Two Widely Used Risk Management Instruments: Crop Insurance and Pesticidesmentioning
confidence: 97%
See 1 more Smart Citation
“…Ifft et al (2014) showed that farm value increased when fields are insured. Kuethe and Morehart (2012) proved that crop insurance improved farmlevel profit in the USA while Zhao et al (2016) did not demonstrate such effect in China. By contrast, only one study by Roberts et al (2003) considered the influence of crop insurance on pesticide use with contrasted results according to the crops considered: they reported a modest reduction of chemical input applications on tobacco and cotton crops and a modest increase on corn.…”
Section: Two Widely Used Risk Management Instruments: Crop Insurance and Pesticidesmentioning
confidence: 97%
“…More specifically, we use difference-in-differences methods and propensity score matching because these methods allow simulating a controlled experiment (Antonakis et al 2010). They have already been used in the literature to measure the effects of crop insurance on debt use (Ifft et al 2015), on profit (Kuethe and Morehart 2012;Zhao et al 2016), and on farm value (Ifft et al 2014). Using this method, we propose to test whether crop insurance purchase has or does not have a negative influence on pesticide expenses and to compare the observed trend with non-insured farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2004, policy-based, multiperil crop insurance (MPCI) has developed rapidly with government fiscal support in China (Wang et al 2011;Xiao and Yao 2019). But the MPCI's sustainability is plagued by high administrative costs, moral hazard, and adverse selection (Berhane et al 2013;Zhao et al 2016;Ye et al 2017). Index-based insurance indemnifies policyholders based on the observed value of an ''index'' that is highly correlated with losses.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that RAL has an important role to play in farmer decision to purchase crop insurance and in their participation in agricultural contracts (Vassalos and Li 2016). In addition, farmers' decision to buy insurance is influenced by insurance experience, farming experience, age, cropland area, harvest failure experience (Zhao et al 2016).…”
mentioning
confidence: 99%
“…The compensation can be used by farmers as capital for farming in the following season. Zhao et al (2016) used Propensity Score Matching (PSM) to assess the impact of farmer participation in crop insurance on farmer income in China. PSM involves an analysis of factors that influence farmer decision to participate in crop insurance by using a logistic regression model.…”
mentioning
confidence: 99%